A Systematic Literature Review of Environmental Education Strategies in Reducing Aedes sp Populations through Natural Attractant-Based Trapping - Purnamasari, A. Bida; Setiawati, Yuliyanti; Sahabuddin, Erma Suryani (Jurnal Biologi Tropis, 2025)
Increasing population density in Indonesia, unmanaged urbanization, and climate change have created ideal conditions for the proliferation of Aedes aegypti and Aedes albopictus. Controlling the Aedes sp. mosquito population is not only a health issue, but also a complex ecological and social issue, requiring an integrated strategy involving science, technology, and public education. This study is a Systematic Literature Review (SLR) that aims to examine educational strategies, their roles, and future development directions for Aedes sp. control. The study was conducted following PRISMA guidelines using the Scopus database for the period 2015–2025. A total of 30 articles were identified, 18 of which met the inclusion criteria and were analyzed thematically to identify patterns, effectiveness, and contributions of educational strategies to changes in people's ecological behavior. The results of the study indicate that school-based educational strategies, community training, public campaigns, and citizen science approaches play a significant role in increasing environmental literacy, social participation, and individual and group ecological responsibility. The integration of local culture and sustainable education policies strengthen the program's success by ensuring broader social acceptance. Existing research remains fragmented and has not fully integrated the dimensions of education, ecology, and public health. Therefore, future research is recommended to develop a transdisciplinary approach through collaboration between educational institutions, government, and local communities to create an adaptive, evidence-based, and sustainable vector control system.